Improving Capital Budgeting Decision With Real Options: A Theoretical And Practical Perspective - Hien, Chin Vui (2009)
This paper will demonstrate the application of Option-pricing models (OPMs), in particular real options value (ROV) and the use of Real Options Analysis (ROA), to enable managers to accomodate flexibility in the investment decision so that the valuation of a project can reflect operating and strategic adaptability.